2017
DOI: 10.1515/phys-2017-0045
|View full text |Cite
|
Sign up to set email alerts
|

Modelling of intermittent microwave convective drying: parameter sensitivity

Abstract: Abstract:The reliability of the predictions of a mathematical model is a prerequisite to its utilization. A multiphase porous media model of intermittent microwave convective drying is developed based on the literature. The model considers the liquid water, gas and solid matrix inside of food. The model is simulated by COMSOL software. Its sensitivity parameter is analysed by changing the parameter values by ±20%, with the exception of several parameters. The sensitivity analysis of the process of the microwav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…However, microwave vacuum drying still induces browning of the fruits and vegetables because of its non-uniform heat [5,14]. To resolve this issue, different types of intermittent drying have been introduced, for example, intermittent microwave convective drying [15], intermittent heat pump drying [16], intermittent microwave convective drying [17], and intermittent microwave-convective air drying [18]. The strategy of applying intermittency allows time to transfer the moisture during the tempering period.…”
Section: Introductionmentioning
confidence: 99%
“…However, microwave vacuum drying still induces browning of the fruits and vegetables because of its non-uniform heat [5,14]. To resolve this issue, different types of intermittent drying have been introduced, for example, intermittent microwave convective drying [15], intermittent heat pump drying [16], intermittent microwave convective drying [17], and intermittent microwave-convective air drying [18]. The strategy of applying intermittency allows time to transfer the moisture during the tempering period.…”
Section: Introductionmentioning
confidence: 99%
“…All samples had a similar distribution of moisture; the moisture concentration was high (4 × 10 4 mol/m 3 ) at the center and up to 3 cm in the radial direction, then sharply decreased from 3 cm to the surface (3.75 × 10 4 mol/m 3 ) of the sample at 5 cm in the radial direction during heating. The results indicated that the moisture content inside the center was higher than at the surface during heating, which might be because water migrated from the internal part of the sample to the surface, transformed into vapor, then vaporized from the surface to the surroundings (Zhang et al., 2017). In addition, at the same heating duration and location, the moisture concentration was significantly higher in the low‐, than the high‐porosity model that had a higher moisture concentration gradient.…”
Section: Resultsmentioning
confidence: 99%
“…The intermittent drying is suitable for the materials susceptible to cracking such as clay‐like materials 5 and heat‐sensitive materials such as food products 4 . Also it can be applied to any kind of dryer systems such as vacuum, 6 microwave convective, 7 microwave vacuum, 8 infrared, 9 fluidized bed, 10,11 and superheated steam dryer 12 . The special advantages of the intermittent drying are that it does not need any additional cost and enhances the efficiency of the existing dryers in terms of energy consumption and dried product quality by changing the drying conditions.…”
Section: Introductionmentioning
confidence: 99%
“…One of the main simplifying assumptions which has been done in many studies dealing with the drying process modeling is neglecting the heat 17 and/or mechanical aspects 7 . Neglecting material properties changes, material deformation and simplified 1D or 2D geometry are the other common simplifying assumptions in drying models.…”
Section: Introductionmentioning
confidence: 99%